SAPU ALANG SEBAGAI IDENTITAS LELAKI SUMBAWA - Aka Kurnia SF; Aswar Tahir; Vivin Nila Rakhmatullah; Muhammad Zuhardiman (KAGANGA KOMUNIKA: Journal of Communication Science, 2023)
This study aims to describe and analyze the signs found in Sapu Alang, such as motives. In order to find out how Sapu Alang became the identity of the Sumbawa people. This research is a qualitative research using Charles Sanders Pierce's semiotic analysis, which is based on representament, object, interpretant. The object in this study is Alang Sapu. This study uses interview data, observation, and documentation. This research focuses on the meaning or meaning of the hidden signs, symbols and symbols in the Sapu Alang motif so that later it will be associated with how Sapu Alang becomes the identity of the people of Sumbawa. The data were obtained through semiotic analysis, while the research location was Poto Hamlet, Poto Village, Moyo Hilir District, Sumbawa. The results of the study after analysis using Carles Sanders Pierce's semiotics show that the reed broom gives signs to objects in the form of various forms of motifs which as a whole show the identity of the Sumbawa people. The identity referred to is as an agrarian society that always maintains harmony with nature and with God the Creator of Nature   Keywords: Sapu Alang, Sumbawa, Semiotic, Visual Communication